Speculative bubble in the housing market in Bogota (2014)
In recent times it has shown a significant increase in housing prices, high recovery in real estate prices in Colombia and the need for households to get a decent place to live has led to the completion of this study, oriented to establish property market fundamentals to establish ¿whether the current economic environment may find symptoms to speak of a misalignment of home prices in Bogota for the past five years? and what lies ahead in a highly dynamic market, heterogeneous and a relatively inelastic supply.